PENGARUH LATIHAN SHUTTLE RUN TERHADAP KELINCAHAN TIM VOLI PUTRI AISYAH RAHAYU PUTRI (ARP) KABUPATE PELALAWAN YANG MENGIKUTI ATLETIK VOLI - Yunani Yunani; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to learn whether there is a Shuttle Run exercise (back and forth) Against the agility of the Aisyah Rahayu Putri Volleyball Team Putri Pelalawan Regency. Held at Putri ARP Volleyball, Bukit Lembah Subur Rt / Rw 002/001 Desa / Kelurahan Bukit Lembah Subur, Kerumutan District, Pelalawan Regency, Postal Code 28386, RIAU Province, in November - July 2020. The population which is also an example of this research is the women's volleyball team Aisyah Rahayu Putri of Pelalawan Regency who received 9 people who are still actively participating in the training. Based on the analysis of the pree and post test data there are differences that increase or increase by 0.22 and based on the t-test analysis produces a tcount of 2.11 and a ttable of 1.860 tcount> ttable, from here it can be used to increase agility on the ARP women's volleyball team in the Regency Pelalawan. Key Words: Shuttle Run Training, Agility